Persepsi Masyarakat Terhadap Isu LGBT Dalam Perspektif Sosiologi Budaya - Rahmat Pannyiwi; Amelia Darwis; Nurhaedah Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) has become a social issue that has sparked controversy in society. Public perception of LGBT is influenced by cultural, religious, educational, and prevailing social values. This study aims to analyze public perceptions of LGBT issues from a cultural sociology perspective. The research method used is qualitative with a descriptive-analytical approach through literature study and interviews. The results of the study show that most people view LGBT as a deviation from local social and cultural norms, although there are groups that are beginning to be more inclusive on the grounds of human rights. From a cultural sociology perspective, these perceptions are formed through the internalization of values, social interaction, and cultural constructs that develop within society.